Basic Hazardous Waste Management, Third Edition - Blackman, William C. (CRC Press, 2009)
This third edition updates and expands the material presented in the best-selling first and second editions of Basic Hazardous Waste Management. It covers health and safety issues affecting hazardous waste workers, management and regulation of radioactive and biomedical/infectious wastes, as well as current trends in technologies. While the topics have been completely revised, the author employs the same practical approach that made the previous editions so popular. Chapters are structured to first outline the issue, subject, or technology, then to describe generic practice, and then to conclude with a summary of the statutory or regulatory approach.